2014
DOI: 10.1039/c4mt00051j
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of zinc deficiency on phagocytosis, oxidative burst, and production of pro-inflammatory cytokines by human monocytes

Abstract: Zinc deficiency has a fundamental influence on the immune defense, with multiple effects on different immune cells, resulting in a major impairment of human health. Monocytes and macrophages are among the immune cells that are most fundamentally affected by zinc, but the impact of zinc on these cells is still far from being completely understood. Therefore, this study investigates the influence of zinc deficiency on monocytes of healthy human donors. Peripheral blood mononuclear cells, which include monocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 38 publications
3
55
1
Order By: Relevance
“…The intracellular distribution of zinc might lead additionally to effective clearance of the intracellular pathogen. 47 This is in accordance with the fact that the presence of zinc is able to inhibit NADPH oxidase with subsequent inhibition of ROS production. In particular, impaired lymphopoiesis was seen in zinc-deficient mice, whereas the numbers of monocytes and neutrophils increased.…”
Section: Antioxidant Effects Of Zinc Within Immune Cellssupporting
confidence: 76%
“…The intracellular distribution of zinc might lead additionally to effective clearance of the intracellular pathogen. 47 This is in accordance with the fact that the presence of zinc is able to inhibit NADPH oxidase with subsequent inhibition of ROS production. In particular, impaired lymphopoiesis was seen in zinc-deficient mice, whereas the numbers of monocytes and neutrophils increased.…”
Section: Antioxidant Effects Of Zinc Within Immune Cellssupporting
confidence: 76%
“…Preclinical models as well as human translational studies have demonstrated that low serum zinc concentrations may exacerbate inflammation through disruption of epithelial barrier function, impaired mucosal immunity, and increasing pro-inflammatory cytokines (2) (9) (11) (12) (13, 14). Lending support to the outcomes of these mechanistic investigations, a recently published prospective study examining 17,776 healthy women who were followed over a 26-year period reported that dietary zinc supplementation was inversely associated with the risk being diagnosed with Crohn’s disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, monocytes and macrophages are more resistant to zinc deficiency and high zinc levels [20]. In the central nervous system (CNS), the effect of zinc administration on neuroinflammation has not yet been completely characterized especially following cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%